Construct validity of the perceived stress scale (PSS-10) in a sample of health professionals in family medicine in Bosnia and Herzegovina - Zaim Jatic; Natasa Trifunovic; Hasiba Erkocevic; Elvira Hasanovic; Irma Dzambo; Aida Pilav (Public Health in Practice, 2023)
Background: The 10-item Perceived Stress Scale (PSS-10) has not been translated into Bosnian, nor has a study been conducted employing a sample of family medicine physicians and nurses to examine the instrument's reliability, validity, and factorial structure. Thus, the goal of this study was to investigate the reliability and construct validity of the Bosnian version of the PSS-10 among family medicine professionals. Study design: Cross-sectional descriptive study provided among healthcare professionals in family medicine, using Google forms questionnaire (PSS-10) in Bosnian language. Methods: Translation of PSS-10 in Bosnian is performed according to the proposed set of standardized guidelines. The questionnaire was sent on the email addresses of family physicians and nurses in whole Bosnia and Herzegovina. The collected data were subjected to reliability testing, exploratory and confirmatory factor analysis, which tested three alternative plausible models suggested by the extant literature: single factor, correlated two-factor and bifactor. Results: A total of 272 out of 440 (RR = 61.3) nurses and physician working in family medicine in Bosnia and Herzegovina completed the PSS-10 Bosnia and Herzegovina version (BH). Participants were aged 25 to 69, with a mean age of 44.7 (±10.55). Most participants were women (86.8%) and physicians (58.8%) with specialisation in family medicine (43%). The overall Cronbach's alpha was 0.87 and the test–retest reliability coefficient was 0.88. Exploratory Factor Analysis yielded 2 factors with eigenvalues of 4.77 and 1.35, accounting for 61.2% of variance. Factor 1 consisted of 6 items representing ‘’perceived distress'’, whereas Factor 2 consisted of 4 items representing ‘’perceived coping’’. The Confirmatory factor analysis indicated a very good fit of this bifactor model to this sample. Conclusions: Our results implies that the PSS-10-BH, as a bifactor model with good reliability and validity, may accurately measure the stress levels of family medicine physicians and nurses.